Collaborative Community Hydrology Research in Northern New Mexico. (December 2013) - Guldan, Steven J.; Fernald, Alexander G.; Ochoa, Carlos G.; Tidwell, Vincent C.
Abstract In New Mexico, increasing demand for water, combined with limited supplies and periodic drought, is placing additional stress on traditional acequia communities. Research on the hydrology of acequia agriculture in northern New Mexico has been carried out in three communities and their associated watersheds and irrigated valleys. Critical to the effort has been the participation of the acequias and individual farmers, ranchers, and other community member stakeholders. Participation in hydrology research included assistance in altering flows in acequias, and access to private property and wells, critical to obtain ground and surface water measurements. Further research that integrated hydrologic data with ecosystem, land‐use, economics, and sociocultural data, via development of a system dynamics model, required community member participation through surveys, interviews, and workshops to develop, calibrate and refine the model.